An integrated micro-computer based qualitative and quantitative superstructure rating system for highway RCDG bridges - Garciano, Lessandro Estelito O. (Animo Repository, 1997)
An integrated micro-computer based qualitative and quantitative superstructure rating system for highway bridges is developed. The purpose of this developed Windows-based software is to evaluate the qualitative condition of the components including the overall condition and to determine the strength of the bridge superstructure. A new approach is introduced in the qualitative condition rating. These improvements are the following: a criteria for quantifying and determining the condition of the various superstructure component, an importance factor for each component under various deterioration degree and a weighed average technique combining the rating of each component with its structural importance to determine the overall rating of the bridge. In the quantitative rating method, the Load and Resistance Factor Method is used instead of the operating and inventory rating.The software consists of three major modules: Bridge Inventory and Data module, qualitative and quantitative module and the on-line help module. These modules interact to perform an integrated superstructure bridge rating system.